The influence of lean six sigma and Kaizen to reduce defect products in automotive industry / Razmah Mahmod, Faizah Mashahadi and Nur Amirah Ashari - Mahmod, Razmah; Mashahadi, Faizah; Ashari, Nur Amirah (Universiti Teknologi MARA Selangor, 2017)
The purpose of this study is to measure the influence of Lean Six Sigma (LSS) and Continuous Improvement (KAIZEN) to reduce the defect products in practising Quality Management System (QMS) for the automotive industry. Data were obtained from questionnaires which has been returned from 78 respondents among production operators in assembly section. The data has been analyzed using the Statistical Package for the Social Sciences (SPSS). Result shown that Lean Six Sigma (LSS) and Continuous Improvement (KAIZEN) have positive influence for solving the problem of defect products. The findings of this study will help the industry for giving serious enforcement and attention for these two methods in reducing the defect products thus will reduce the scrap management cost. This study contributes to the advancement of knowledge on methods to reduce defect products for automotive industry.